Electrophoretically mediated microanalysis for simultaneous on-capillary derivatization of standard amino acids followed by micellar electrokinetic capillary chromatography with laser-induced fluorescence detection - Celá, Andrea; Mádr, Aleš; Glatz, Zdeněk (Journal of chromatography. A, Including electrophoresis and other separation methods, 2017)
Amino acids are crucial compounds involved in most biochemical processes essential for life. Since their dynamic turnover reflects the actual physiology of the cell/organism, a turnover assessment may provide valuable information related to multiple physiological and pathophysiological conditions. The sensitive determination of amino acids is predominantly associated with their derivatization which might be laborious, time-consuming and difficult to standardize. However, capillary electrophoresis offers the automatic injection and mixing of reactants, incubation of the reaction mixture, separation and detection of the reaction products in one on-capillary procedure. Among the on-capillary mixing strategies, electrophoretically mediated microanalysis (EMMA) is superior in terms of mixing efficiency. In this paper, we present an optimization of EMMA for the simultaneous derivatization of standard amino acids by naphthalene-2,3-dicarboxaldehyde/NaCN and its application to targeted human embryo metabolomics. For such a purpose, novel separation conditions were developed involving the background electrolyte, comprised of 73mM sodium dodecyl sulfate, 6.7 % (v/v) 1-propanol, 0.5mM (2-hydroxypropyl)-β-cyclodextrin and 135mM boric acid/sodium hydroxide buffer (pH 9.00). Finally, the optimized EMMA was compared to a fundamentally different mixing strategy, namely the transverse diffusion of laminar flow profiles, and proved to be also suitable for human plasma analysis.
Keywords: aminokyseliny; Amino Acids; krevní plazma; beta-Cyclodextrins; fluorescence; beta-cyklodextriny; Humans; Chromatography, Micellar Electrokinetic Capillary; hydroxypropyl beta cyklodextrin; lidé; 2-Hydroxypropyl-beta-cyclodextrin; Plasma; chromatografie micelární elektrokinetická kapilární; Fluorescence